Chronique juridique - Létourneau, Alain; Moreau, Rémi (Assurances, 1982)
Mr. Alain Létourneau studies the rights of the mortgagor following an intentional fault of the insured. This is certainly an interesting point as one may well wonder to what extent the insured's fault renders the insurance null and void. Mr. Létourneau considers the effects of the Civil Code and jurisprudence. Mr. Rémi Moreau considers the court's interpretation of the expression "Claims made".